Vertical Transmission of Overweight: Evidence from English Adoptees - Joan Costa-i-Font; Mireia Jofre-Bonet; Julian Le Grand (Center for Economic Studies and ifo Institute (CESifo), 2015)
We examine the vertical transmission of overweight drawing upon a sample of English children, both adopted and non-adopted, and their families. Our results suggest strong evidence of an intergenerational association of overweight among adoptees, indicating transmission through cultural factors. We find that, when both adoptive parents are overweight, the likelihood of an adopted child being overweight is between 10% and 20% higher than when they are not. We also find that the cultural transmission of overweight is not aggravated by having a full-time working mother, so do not confirm the existence of a female labour market participation penalty on child overweight among adoptees. Overall, our findings, despite subject to data limitations, are robust to a battery of robustness checks, specification and sample selection corrections.
Keywords: I18; D13; Z10; 330; vertical transmission; cultural transmission; overweight; children; natural parents; Body Mass Index; sample selection